Evaluation of the association between malaria infection and electrolyte variation in patients: Use of Pearson correlation analytical technique - James A. Ndako; Joseph A. Olisa; Ogechukwu Y. Ozoadibe; Victor T. Dojumo; Victor O. Fajobi; Jeremiah A. Akinwumi (Informatics in Medicine Unlocked, 2020)
Background: Malaria is a mosquito borne serious infectious disease caused by the protozoan parasites of the plasmodium species. Plasmodium vivax and P. falciparum are the common causes of malaria infection. Electrolytes play an important role in the normal functioning of human body. Malaria infection has been shown to be associated with abnormalities in fluids, electrolytes and acid base balance which are capable of enhancing disease severity. This study evaluates the relationship between malaria infections and electrolytes among malaria infected patients. Methods: Finger prick blood samples were collected from Two-Hundred (200) malaria-suspected patients. The Giemsa-stained blood smears were carefully examined according to standard procedure. Relevant information from each subject was obtained using well-structured questionnaires. Results: Pearson's Correlation Coefficient technique was used to investigate the relationship, and the strength of association between the variables. The mean bound of patients' sodium level was observed to fall within the specified normal limits of 125 mmol/L – 145 mmol/L; except for positive malaria patients belonging to the MP-(++) which will fall below the 125 mmol/L (i.e. 126.25 mmol/L – 1.77 mmol/L = 124.48 mmol/L). Conclusion: This study discovered a significant linear relationship based on the Pearson product-moment correlation between creatinine and urea, potassium and chloride, potassium and creatinine, potassium and urea. The mean sodium and chloride level of positive malaria [MP-(++)] patients were observed to fall outside the normal limit. It was also found that Plasmodium falciparum showed more alteration in electrolytes parameters than Plasmodium vivax.